Aplikasi Pembuatan E-Commerce Pada Toko X - Hans Kurniawan Soetanto; Leo Willyanto Santoso; Alexander Setiawan (Jurnal Infra, 2016)
X Store is a company in Salatiga which their focus on selling computer accessories. In doing their business process, all sales is recorded in store/offline. After their company close, there is no sales after. Because they don’t have any online system. The other way to do sales, they use BBM, whatsapp, and email to contact selling department. The problems encountered, that selling department got hardly to maintain one by one phone call. Based on this background, application is designed to overcome the problems.Application was build based on website that can accessed by customer to do transaction by their phone or computer. This website help customer to do transaction such as choosing item, payment, packaging, and delivery their item. Lastly, confirmation transaction e-mail for customer. The website was build using PHP as the programming language and MySQL databases.Overall this website meets the company requirements and help customer to do transaction. This proven by 80% is satisfied with the website and 60% is quite satisfied with the completeness information.